Storage Time of Freshwater Lobster (Cherax quadricarinatus) with Green Betel Leaf Anesthesia (Piper betle L) - Muhammad Haekal Tiftazani; Suparmi Suparmi; Sumarto Sumarto (Berkala Perikanan Terubuk, 2022)
Freshwater lobster (Cherax quadricarinatus) is a freshwater fishery commodity that has a very promising selling price. The price of live freshwater lobster can be sold up to Rp. 250,000/kg and frozen to death at a price of Rp. 100,000 in Pekanbaru. The export value of lobster commodities in Indonesia grows by an average of 3.54% per year. One way to maintain the life of the lobster during the lobster export process is by means of a dry system of live transportation. Giving natural anesthetics can use green betel leaf extract. The purpose of this study was to determine the storage time of freshwater crayfish (Cherax quadricarinatus) given natural anesthesia with green betel leaf extract (Piper betle L). This study used a laboratory experimental method with a non-factorial completely randomized design (CRD) as the treatment was storage time consisting of 4 levels of treatment, namely 6, 12, 18, and 24 hours and repeated 3 times. The test parameters of this study were the length of time awake, survival, and body weight loss of lobster during storage. The best treatment in this study was K2 a storage time of 12 hours getting survival rates of up to 90% and body weight loss during storage of 3%.